Analisis Hasil Tangkapan Di Perairan Umum Daratan Krueng Aceh - Rivan Febrian; Faisal Syahputra; Kurnia Kurnia (Center for Research and Community Service (LPPM) University of Abulyatama, 2023)
Aceh has considerable potential for inland public aquatic resources. One of the important inland waters is Krueng Aceh, Krueng Aceh is a river located in Aceh Province in Cot Seukek, Aceh Besar Regency, passing through the city center (Peunayong) and empties into Lampulo Banda Aceh City. Analysis of catches in Krueng Aceh was carried out with the aim of determining the types of fish in the public waters of the Krueng Aceh mainland as basic data in the management of mainland public water resources. The study used the Purposive sampling technique at four stations and the results showed that there were 9 types of fish in the public waters of the Krueng Aceh mainland which were dominated by baung fish. The station with the most catches is station II located at Bakoy Village, Ingin Jaya District, Aceh Besar District. There are 4 types of fishing gear that are commonly used in the public waters of the Krueng Aceh mainland and gill net fishing gear is the most effective fishing gear used.